Low-Field MR Imaging of Meningiomas Including Dynamic Contrast Enhancement Study: Evaluation of Surgical and Histopathologic Characteristics - Yrjänä, S.K.; Tuominen, H.; Karttunen, A.; Lähdesluoma, N.; Heikkinen, E.; Koivukangas, J. (American Journal of Neuroradiology, 2006)
BACKGROUND AND PURPOSE:Risks associated with surgery of meningiomas, especially those located in the skull base, are influenced by tumor consistency and vascularity. The purpose of this study was to find out if vascularity, consistency, and histologic characteristics of meningioma can be predicted preoperatively by using low-field MR imaging, including dynamic imaging of contrast enhancement.MATERIALS AND METHODS:Twenty-one patients (mean age, 56; range, 34–73 years; 16 women, 5 men) with meningioma requiring first surgery were imaged by a 0.23T scanner. Time to maximum enhancement, maximum enhancement, and maximum intensity increase were noted from the enhancement curve of dynamic imaging. Relative intensity of tumor in fluid-attenuated inversion recovery (FLAIR) and T2-weighted images was calculated. The neurosurgeon evaluated surgical bleeding and hardness of tumor on a visual analog scale. Histopathologic analysis included subtype, World Health Organization grade, mitotic activity, grades of progesterone receptor expression and collagen content, proliferation activity by Ki-67 (MIB-1), and microvessel density by CD34. Correlations were studied with Kendall τ statistics.RESULTS:The most powerful association was found between time to maximum enhancement and microvessel density (τ = −0.60, P < .001). Surgical bleeding (τ = 0.49, P = .002), blood loss during surgery (τ = 0.49, P = .002), progesterone receptor expression (τ = 0.59, P < .001), and collagen content (τ = −0.54, P < .001) were statistically best correlated with the relative intensity of meningioma on FLAIR images. Tissue hardness correlated best with relative intensity on T2-weighted images (τ = 0.40, P = .012).CONCLUSION:Assessment of microvessel density, collagen content, and progesterone receptor expression of meningioma may be clinically feasible by using low-field MR imaging.